Analysis on Islamic home financing in Malaysia / Azwina Wati Abdull Manaf, Siti Marshita Mahyut and Asfarina Kartika Shakri - Abdull Manaf, Azwina Wati; Mahyut, Siti Marshita; Shakri, Asfarina Kartika (Academy of Contemporary Islamic Studies (ACIS), 2017)
Islamic financial institutions (IFIs) realize that they need to innovate and create new products in order to remain competitive with the conventional products. In introducing Islamic home financing, Islamic banking has used several Islamic concepts such as Ijarah (leasing), Istisna’ (purchase order) and Musharakah Mutanaqisah (partnership) to create more flexible products and provide more options for the people to choose the kind of products that suit them the most. Islamic home financing product is also considered as an alternative product to conventional housing loan with its own specialties to be discussed later. In introducing new product, Bank Negara Malaysia plays an important role in providing guidelines for the IFIs to adhere to in innovating or developing to serve the interest of the customers. This paper analyses in detail on how Islamic finance concepts are used and applied by the IFIs to introduce different types of home financing products.